OBE Unit activities in year 2023 / Norlizan Wahid … [et al.] - Wahid, Norlizan; Ahmad, Hazrina; Ismail, Badrul Nizam; Juhari, Nurjuhanah (Unit Penerbitan PKAPP, 2024)
In 2023, our faculty's OBE unit led various activities to enrich teaching and learning, all geared towards enhancing our program outcomes. These efforts were aimed at improving the overall educational experience and fostering academic excellence through various initiatives. Two presentations on CDL-CQI were conducted, on March 23rd and another on September 21st, for the semesters of 20224 and 20232, respectively. These sessions were carried out to showcase the analysis of the program outcomes attainment for both CEEC110 and CEEC221 programs, serving the purpose of continual quality improvement. The presentations were delivered to faculty members to ensure collective awareness of the overall Program Outcome (PO) attainment, facilitating targeted improvements in individual courses across the faculty.